EFEKTIFITAS KINERJA PELAYANAN SENSUS PENDUDUK BERBASIS ONLINE DI BADAN PUSAT STATISTIK KOTA MALANG - Sukma Faradiba; Slamet Muchsin; Hayat Hayat (Sekolah Tinggi Pariwisata Mataram, 2021)
The Central Bureau of Statistics of Malang City is a Non-Ministerial Government Institution that is directly responsible to the President who is in Malang City, located on Jl. West Janti. No. 47, Bandungrejosari, Sukun District, Malang City, East Java 65148. This study aims to determine the effectiveness of the online-based population census service performance as well as the supporting and inhibiting factors in the implementation of the online-based population census at the Central Statistics Agency of Malang City. This research method uses a qualitative method with a descriptive approach. The method of data collection is by conducting interviews, observation and documentation. The analysis technique used is data reduction, then data display (data presentation) and conclusions: drawing/veritifying (withdrawal of conclusions). The results of this study indicate that there are several performances of online population census services at BPS Malang City to the community, including by conducting socialization related to online SP both through social media and mass media. Regarding the inhibiting factors or obstacles faced by the Malang City BPS in conducting the online population census, namely the lack of available budget funds and so on. And can determine how effective the performance of online-based population census services is.